Peningkatan Kompetensi Guru Ciayumajakuning Melalui Bimbingan Teknis Teknologi AI Gemini - Dadang Sudrajat; Denni Pratama; Fatkhan Mubarok; Muhammad Zamil Farhan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The advancement of Artificial Intelligence (AI) technology has created significant transformations across various sectors, including education. However, the adoption of AI in the educational sector—particularly in the Ciayumajakuning region (Cirebon, Indramayu, Majalengka, and Kuningan)—still faces several challenges, such as low digital literacy among teachers, limited access to technological training, and a lack of understanding regarding the practical application of AI in learning and school administration contexts. The Gemini AI Technical Training Program is part of a Community Service initiative aimed at enhancing teachers' capacity to use AI technology in a practical and ethical manner within educational environments.